Front-end development and deployment of local-based speech recognition system - Lee, Owen Jun Hao (Nanyang Technological University, 2024)
This Final Year Project focuses on enhancing and locally deploying SG Decoding, a full stack web application for multilingual speech recognition and transcription. The primary objectives were to refine the front-end interface, optimize performance, and adapt the system for offline use while maintaining its core functionalities.